Clampless non descent vaginal hysterectomy: “A novel art” - Nalini, Neelam; ., Bijeta; Singh, Shreshtha; Singh, Harsh Vardhan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of this study was to assess feasibility and safety of clampless non descent vaginal hysterectomy of uterus up to 16 weeks size and identifying factors that determine success of surgery. Methods: Study was conducted in 50 women with non-prolapsed uteri, with clear cut indication of hysterectomy for a benign cause, without suspected adnexal pathology. Operating time, estimated blood loss, surgical techniques, difficulties encountered during operation, operative and post-operative complications and conversion to laparotomy when needed were recorded. Results: Vaginal hysterectomy was successful in 47 cases. Bisection was required in 60% cases, myomectomy in 24% cases and morcellation in 16% cases. Amount of blood loss and operating time was proportional to size of uterus. Conclusions: Clampless non descent vaginal hysterectomy is a safe and effective procedure and for success not only size of the uterus but its all dimensions and location of fibroid should be taken into consideration.